Quizlet: A Digital Media for Learning Informatics Terms - Hikmah, Durratul; Hannan, Abdul (Universitas Nurul Jadid, 2019)
Learning informatics terms in English conventionally make students learn passively and concern with the lecturer being the controller of the learning environment.